Safety and efficacy of the HilumDirect uVATS for small cell lung cancer: a retrospective study - Zhang, Xining; Liu, JingWei; Zhang, Shijie; Li, Jian (Frontiers in Surgery, 2025)
BackgroundDespite advancements in multidisciplinary treatments, long-term survival rates for small cell lung cancer (SCLC) patients remain poor, and the role of surgical resection has been debated since the late 20th century. A more comprehensive surgical approach is necessary to enhance local control and improve outcomes.MethodThe records of the patients who received surgical treatment between January 2015 and December 2020 were collected and analyzed with propensity-score matching. The preoperative characteristics, short-term outcomes, and long-term survival were analyzed and compared between the HilumDirect uVATS and the conventional uVATS groups.ResultsPreoperative variables were well-balanced between the two groups. The HilumDirect uVATS group showed a numerically higher lymph node yield. Patients in the HilumDirect uVATS group pointed toward a numerical difference in cancer-specific survival (CSS) and recurrence-free survival (RFS) compared to the Conventional resection group (CSS, 50.82% vs. 44.09%, p = 0.890, RFS, 42.86% vs. 38.46%, p = 0.904). This numerical difference was consistent in both lymph node-negative (CSS: 72.70% vs. 51.60%, p = 0.287, RFS: 58.30% vs. 47.60%, p = 0.654) and node-positive subgroups (CSS: 35.70% vs. 33.30%, p = 0.869, RFS: 31.20% vs. 22.22%, p = 0.833). Competing risks analysis suggested a non-significant difference in the lower risk of distal metastasis of the HilumDirect uVATS (Subdistribution hazard ratio of Conventional uVATS: 2.164, 95% CI 0.741–6.318, p = 0.158).ConclusionThe HilumDirect uVATS resection can be safely performed by experienced surgeons with minimal invasiveness. Our findings suggest that selected SCLC patients, particularly those with positive lymph nodes, may benefit from this approach. However, further studies are warranted to confirm these results.